The Hellenistic period: the era of the Diadochi - André, Alessandra (Romanitas - Revista de Estudos Grecolatinos, 2015)
Review of: ANSON, E. M. Alexander’s heirs: the age of successors. Oxford: Oxford University Press, 2014. 248 p.
Keywords: Hellenistic Greece; Alexandre; Dyadocs; Power